Implementation outcomes of peer education programme comparing state-led and NGO-facilitated models in two Indian states: qualitative findings - Arora, Monika; Bassi, Shalini; Bahl, Deepika; Thapliyal, Nishibha; Kumar, Deepak; Pemde, Harish K.; Rizvi, Zoya Ali (Frontiers in Public Health, 2024)
IntroductionEach Indian state can select one of the two implementation models under India’s National Adolescent Health Strategy, i.e., Rashtriya Kishor Swasthya Karyakram, either direct implementation through the existing State Health Department and systems, or the Non-Governmental Organisation (NGOs) implementation model, which involves partnering with one or more field-level NGOs to provide the services and personnel.MethodsTo compare and comprehend the implementation strategies of the Peer Education programme under the Direct and NGO implementation models within India’s National Adolescent Health Strategy, and to document factors facilitating and hindering the adoption and implementation of the programme across two Indian states, using a qualitative approach.ResultsVariations and similarities were seen across the two models. Employing a multi-level selection process, Madhya Pradesh selected two peer educators (PEs), while Maharashtra had four. Criteria included adolescents aged 15 and above in Madhya Pradesh and younger (10–14 years) and older (15–19 years) in Maharashtra. Madhya Pradesh selected Shadow Peers (10–14 years) to address attrition. Training in Madhya Pradesh spanned over 6 days, structured, led by NGO Mentors, utilising standardised, interactive resources with participatory methods. Maharashtra’s training, facilitated by Auxiliary Nurse Midwife or Medical Officer, followed traditional approaches and relied on the trainer’s expertise. PE session frequency and duration varied from monthly to quarterly. PEs were comfortable in handling issues like nutrition and non-communicable diseases but faced hesitancy in handling sexual and reproductive health issues. Regular Adolescent Friendly Clubs supported peer educators (PEs). In Madhya Pradesh, Adolescent Health and Wellness Days were suspended due to the pandemic, which led to decreased awareness of adolescent health services. Maharashtra resumed Adolescent Health and Wellness Days albeit on a limited scale.ConclusionThe study identified various similarities and deviations from operational guidelines for the implementation of the peer education programme, offering valuable guidance for policymakers, practitioners, and stakeholders involved in RKSK’s planning and implementation. It presents actionable strategies to strengthen peer education interventions within national adolescent health programmes, regionally and globally.